Elution Adsorption Dynamics of Organic Substances on Carbon Adsorbents - N.S. Polyakov; A.V. Larin; M.L. Goubkina (Adsorption Science & Technology)
Breakthrough curves of CF 3 Cl on carbon black and of cyclo-hexane on active charcoal have been measured under elution adsorption dynamic conditions. For linear and non-linear adsorption dynamic modes, the experimental data and theoretical results calculated according to the layer of equilibrium adsorption (LEA) model closely coincide.